ASSESSING THE INFLUENCE OF SPORTS FACILITY ON CUSTOMER SATISFACTION AT CHULALONGKORN UNIVERSITY SPORTS CENTER - Tongsook, Utaiwan; Gulthawatvichai, Tepprasit (Journal of Sports Science and Health, 2019)
Sports Center in University is a place to support students and university employees as well as local people who live in surrounding areas in order to play sports and do exercise. Chulalongkorn University Sports Center is authorized and under the control of Chulalongkorn University. Furthermore, it has a contemporary feel and easy to access. Purpose The purpose of this study aimed to study sport facilities influencing on customer satisfaction at Chulalongkorn University Sports Center. Methods The samples include 400 customers who used sport facility at Chulalongkorn University Sports Center. Questionnaires were used as research instrument. The data were analyzed using descriptive statistics including frequency, mean, and standard deviation. Research hypothesis was tested by using multiple regression. Results The results showed that most respondents were male, aged between 18 and 29 years old, single, and granted bachelor’s degree. Most of the customers were students. The results of the sports facilities influencing on customer satisfaction at Chulalongkorn Sports Center based on Multiple Regression revealed that sports facilities at Chulalongkorn University Sports Center in terms of physical aspect, main products, and service personnel had influenced on customer satisfaction with statistical significance of 0.05, with main products gaining the highest satisfaction, followed by physical aspect, and service personnel respectively. Conclusion Sports facilities at Chulalongkorn University Sports Center in terms of physical aspect, main products, and service personnel had influenced on customer satisfaction.